Perspective: Opportunities and Challenges of Technology Tools in Dietary and Activity Assessment: Bridging Stakeholder Viewpoints. Issue 1 (20th September 2021) - Das, Sai Krupa; Miki, Akari J; Blanchard, Caroline M; Sazonov, Edward; Gilhooly, Cheryl H; Dey, Sujit; Wolk, Colton B; Khoo, Chor San H; Hill, James O; Shook, Robin P
Abstract: The science and tools of measuring energy intake and output in humans have rapidly advanced in the last decade. Engineered devices such as wearables and sensors, software applications, and Web-based tools are now ubiquitous in both research and consumer environments. The assessment of energy expenditure in particular has progressed from reliance on self-report instruments to advanced technologies requiring collaboration across multiple disciplines, from optics to accelerometry. In contrast, assessing energy intake still heavily relies on self-report mechanisms. Although these tools have improved, moving from paper-based to online reporting, considerable room for refinement remains in existing tools, and great opportunities exist for novel, transformational tools, including those using spectroscopy and chemo-sensing. This report reviews the state of the science, and the opportunities and challenges in existing and emerging technologies, from the perspectives of 3 key stakeholders: researchers, users, and developers. Each stakeholder approaches these tools with unique requirements: researchers are concerned with validity, accuracy, data detail and abundance, and ethical use; users with ease of use and privacy; and developers with high adherence and utilization, intellectual property, licensing rights, and monetization. Cross-cutting concerns include frequent updating and integration of the food and nutrient databases on which assessments rely, improving accessibility and reducing disparities in use, and maintaining reliable technical assistance. These contextual challenges are discussed in terms of opportunities and further steps in the direction of personalized health. Abstract : Statement of Significance : This article is the first to discuss the status and challenges of current and emerging technology tools designed to measure individual food intake, eating behavior, and physical activity through the perspectives of 3 stakeholders: researchers, users, and developers. The objective of this work is to bring together experts to address interdisciplinary and cross-cutting issues with the shared mission of improving the measurement of energy intake and expenditure.